Confessions and boundaries in the Holy Roman Empire: The Brandenburg, Minden, and the Calendar in 1668 - Christophe Duhamelle (L'Atelier du CRH)
Between 1583 and 1700, there were two calendars in use in the Holy Empire, with a gap of ten days between them. It is generally said that one of the calendars, the Gregorian, was Catholic, and the other, the old Julian calendar, was Protestant. There is no theological reason for this division, nor is it absolute, a fact demonstrated by the case studied in this article. In 1668, the Elector of Brandenburg (Protestant) imposed a transition to the (supposedly Catholic) Gregorian calendar on his subjects of the principality of Minden in Westphalia (with a Protestant majority). The arguments of the various protagonists in this decision and the debates it engendered reveal synergies and shifts between the religious and other domains (including economic), warping these categories that are often reified in historiography. Moreover, the debate shows that Minden’s border was embedded in the variety of scales that were mobilized according to their particular interests by various actors. This case study thus permits us to re-situate spatial and category-specific boundaries – which seem consubstantial with the notion of the territorial State in the Empire – in a complex social game that can only be understood through a wide range of sources.